2022
DOI: 10.1109/tnsre.2022.3161272
|View full text |Cite
|
Sign up to set email alerts
|

Federated Deep Learning for the Diagnosis of Cerebellar Ataxia: Privacy Preservation and Auto-Crafted Feature Extractor

Abstract: Cerebellar ataxia (CA) is concerned with the incoordination of movement caused by cerebellar dysfunction. Movements of the eyes, speech, trunk, and limbs are affected. Conventional machine learning approaches utilizing centralised databases have been used to objectively diagnose and quantify the severity of CA. Although these approaches achieved high accuracy, large scale deployment will require large clinics and raises privacy concerns. In this study, we propose an image transformation-based approach to lever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…T ρ+T η T ρ+T η+F ρ+F η * 100 [10], [38], [13], [36], [58], [46], [47], [28], [77], [35], [7], [79], [64], [29], [1], [85], [9], [53], [25], [51], [66], [17], [45], [50] Sensitivity (Recall)…”
Section: Measures Equation References Accuracymentioning
confidence: 99%
“…T ρ+T η T ρ+T η+F ρ+F η * 100 [10], [38], [13], [36], [58], [46], [47], [28], [77], [35], [7], [79], [64], [29], [1], [85], [9], [53], [25], [51], [66], [17], [45], [50] Sensitivity (Recall)…”
Section: Measures Equation References Accuracymentioning
confidence: 99%
“…According to research [64], a lightweight convolutional architecture (MobileNetV2) with a recurrence plot transformer could successfully identify 86.69% of cases for Cerebellar Ataxia. The installation of DL-based FL algorithms resulted in a reduction in the amount of money that the service provider spent on operational expenses [65].…”
Section: ) Cerebellar Ataxia Detectionmentioning
confidence: 99%
“…Univariate analysis: Lateral velocity of COM were higher in CA individuals than healthy controls. IMU wearable sensor (2022) [8], [34], [56], [103]- [105] Wearable sensors IMU capture ataxic balance.…”
Section: Optical Tracking Camera-based System (2009 -2016) [99] [102]mentioning
confidence: 99%
“…For instance, research in PD showed the high frequency (3 Hz to 8 Hz) components of leg movements during Freezing of Gait (FOG) were not present in ordinary walking or standing. By calculating a power ratio of the "freeze" band [3][4][5][6][7][8] to the "locomotor" band [0.5-3 Hz], the authors could estimate a threshold to identify FOG events [194]. With a similar method, Handojoseno et al proved the power spectral density and wavelet energy of electroencephalography (EEG) could function as promising biomarkers to indicate FOG with 80% accuracy [195].…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation